TOLERANSI UPAYA UNTUK MEWUJUDKAN KERUKUNAN UMAT BERAGAMA - Hertina Hertina (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2009)
Tolerance in Islam is very comprehensive cover. Therefore, tolerance would not be straight if not born from the heart. This means of tolerance not only requires the willingness to accept differences, but also requires the sacrifice of material and spiritual, physically and emotionally. It was here, the Islamic concept of tolerance (as-samahah) became the basis for Muslims to perform mu'amalah (hablum bond passage) which is supported by strong spiritual connection (hablum minallāh). However, according to Islamic religious tolerance is not to fuse together in faith. Nor to exchange beliefs among groups of different religions. Tolerance here is in terms mu'amalah (social interaction). So, there are limits with what can and can not be violated. This is the essence of tolerance in which each party to maintain control and provide a space for mutual respect of each uniqueness without feeling threatened beliefs and their rights.